2017
DOI: 10.1103/physrevb.95.245414
|View full text |Cite
|
Sign up to set email alerts
|

Gate-dependent spin Hall induced nonlocal resistance and the symmetry of spin-orbit scattering in Au-clustered graphene

Abstract: Engineering the electron dispersion of graphene to be spin-dependent is crucial for the realization of spin-based logic devices. Enhancing spin-orbit coupling in graphene can induce spin Hall effect, which can be adapted to generate or detect a spin current without a ferromagnet. Recently, both chemically and physically decorated graphenes have shown to exhibit large nonlocal resistance via the spin Hall and its inverse effects. However, these nonlocal transport results have raised critical debates due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Only by taking into account all terminal injections one obtains correct results. The pictures usually drawn in experimental studies of spin and valley Hall effects [63][64][65][66][67][68][69][70] can be misleading as they indicate that the electrons injected from the source terminal flow to neighboring terminals (depending on the spin or the valley degree of freedom) other than the drain terminal. This would imply breaking of charge conservation.…”
Section: A General Discussionmentioning
confidence: 99%
“…Only by taking into account all terminal injections one obtains correct results. The pictures usually drawn in experimental studies of spin and valley Hall effects [63][64][65][66][67][68][69][70] can be misleading as they indicate that the electrons injected from the source terminal flow to neighboring terminals (depending on the spin or the valley degree of freedom) other than the drain terminal. This would imply breaking of charge conservation.…”
Section: A General Discussionmentioning
confidence: 99%
“…Synthesis and transfer of graphene. A monolayer graphene was grown on a polycrystalline Cu foil using a chemical vapor deposition method demonstrated elsewhere 23 . 25 μm copper foil (Alfa Aesar, 99.8% purity) was electropolished in phosphoric acid for 15 min and rinsed with distilled water followed by isopropyl alcohol (IPA).…”
Section: Methodsmentioning
confidence: 99%
“…Electron band structure of pristine graphene has been extensively studied over the last decade because of its unusual transport properties 8,9 , and it has been shown that physical properties of graphene can be strongly modified when it is functionalized with various adatoms [10][11][12][13][14][15][16][17][18][19][20][21][22][23] , or proximity effect from heterostructures [24][25][26][27][28][29][30] . Disordered graphene by heavy adatoms could exhibit diverse condensed matter phenomena such as spin Hall effect and QSH state (topological insulator state) due to the instilled spin-orbit coupling and honeycomb lattice distortion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among all intercalants, Au has shown the possibility to result in n-type or p-type doped graphene depending on the amount of gold that is intercalated [14,15]. In addition to controlling the doping type, Au is attractive because it could lead to enhancing spin-orbit interaction (SOI) in graphene, which holds promises for a variety of spin-related phenomena in graphene [16][17][18][19]. From a practical point of view, the chemical inertness of Au is also attractive, because it can enable the ex situ processing of intercalated graphene into devices.…”
Section: Introductionmentioning
confidence: 99%